Anti-influenza virus cytotoxic T lymphocytes recognize the three viral polymerases and a nonstructural protein: responsiveness to individual viral antigens is major histocompatibility complex controlled. - Bennink, J R (1987)
It has recently been shown that antiviral major histocompatibility complex class I-restricted cytotoxic T lymphocytes can recognize proteins that serve as internal viral structural components (influenza A virus nucleoprotein, vesicular stomatitis virus nucleocapsid protein). To further examine the role of internal viral proteins in cytotoxic T-lymphocyte recognition, we constructed recombinant vaccinia viruses containing individual influenza A virus genes encoding three viral polymerases (PB1, PB2, PA) and a protein not incorporated into virions (NS1). We found that cells infected with each of these recombinant vaccinia viruses could be lysed by anti-influenza cytotoxic T lymphocytes. Cytotoxic T-lymphocyte responsiveness to the individual viral antigens varied greatly between mouse strains. By using congenic mouse strains, responsiveness to PB1 and PB2 was found to cosegregate with major histocompatibility complex haplotype. These findings provide further evidence that internal antigens play a critical role in cytotoxic T-lymphocyte recognition of virus-infected cells. Additionally, they suggest that the cytotoxic T-lymphocyte response to viral antigens may often be restricted to only a fraction of the major histocompatibility complex class I repertoire.